2015
DOI: 10.1161/circulationaha.113.007394
|View full text |Cite
|
Sign up to set email alerts
|

Transdifferentiation of Human Fibroblasts to Endothelial Cells

Abstract: Background Cell fate is fluid, and may be altered experimentally by the forced expression of master regulators mediating cell lineage. Such reprogramming has been achieved using viral vectors encoding transcription factors. We recently discovered that the viral vectors are more than passive vehicles for transcription factors, as they participate actively in the process of nuclear reprogramming to pluripotency by increasing epigenetic plasticity. Based on this recognition, we hypothesized that small molecule ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
169
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 156 publications
(174 citation statements)
references
References 31 publications
4
169
1
Order By: Relevance
“…3a) and then subjected them to functional assays to assess their endothelial phenotype. Specifically, we tested the inherent ability of ECs to form three-dimensional vascular networks or uptake acetylated low-density lipoprotein (Ac-LDL) [6]. Consistent with our wire myography data, primary ECs isolated from the PPCM patient’s LADs showed a decreased capacity to form networks of tubular structures when placed on ma­trigel compared to primary ECs isolated from healthy controls (Fig.…”
Section: Methods and Resultsmentioning
confidence: 78%
“…3a) and then subjected them to functional assays to assess their endothelial phenotype. Specifically, we tested the inherent ability of ECs to form three-dimensional vascular networks or uptake acetylated low-density lipoprotein (Ac-LDL) [6]. Consistent with our wire myography data, primary ECs isolated from the PPCM patient’s LADs showed a decreased capacity to form networks of tubular structures when placed on ma­trigel compared to primary ECs isolated from healthy controls (Fig.…”
Section: Methods and Resultsmentioning
confidence: 78%
“…These induced endothelial cells were also verified by a series of functional assays both in vivo and in vitro. 82 …”
Section: Direct Reprogramming Of Vascular Cellsmentioning
confidence: 99%
“…Similarly, his group has shown that the transdifferentiation of fibroblasts to endothelial cells requires activation of innate immune pathways. 2 More recently, his group has preliminary data that innate immune activation of inducible NO synthase results in nitrosylation of epigenetic modifiers that causes a release of suppressive epigenetic mechanisms. Dr Daniel J. Garry (University of Minnesota) presented his recent works on cardiac progenitors that reside in the adult heart and emphasized that the role cardiac progenitor cells during aging and after injury remains unclear but represents an area of active investigation.…”
Section: Cell Therapy Sessionmentioning
confidence: 99%